Peningkatan Sosialiasi Pelayanan Publik Satu Pintu tentang Perijinan Usaha bagi Pedagang Usaha Mikro Pasar Kaget Pagi Jalan Elang Raya, Pondok Timur Indah, RT.05/RW.04, Kel. Mustikasari, Kec. Mustikajaya, Kota Bekasi - Habsulhadiprasodjo Nurhadi; Dodi Rahmat Setiawan; Wahidin Septa Zahran; Rousdy Safari Tamba; Yusup Rachmat Hidayat (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
Micro Business or Street Vendors are basically informal sector traders. In general, the Informal Sector are small-scale unofficial business units that produce and distribute goods and services without having a business license and or location permit based on the provisions of the applicable laws and regulations.The purpose of this community service is to provide insight and knowledge about administrative procedures in the process of obtaining business licenses to obtain business legality, both through licensing services at the Mustika Jaya District office, as well as through licensing services at the One-Stop Integrated Investment and Licensing Service Office ( PMPTSP) Bekasi City and also provided outreach regarding the mechanism and terms of loans that can be made by Pasar Pagi traders to pawnshop city of Bekasi in particular.The method used is conventional counseling or socialization activities, which are carried out face-to-face. The results of this community service indicate an increase in participants' insight and understanding of the mechanisms and requirements for business permits and loans at pawnshop city of Bekasi.